Floor Exercise Digital Book Using the Circuit Elephant Game to Improve the Accuracy of Forward Roll Movements in Elementary School Students - Mujiono; Andrinugroho, Aryo; Buchori, Achmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Field observations show that many elementary school students still have difficulty performing forward rolls correctly. This study aims to develop digital learning media as an interactive book combining elements of the game